OP0167 Prevalence of Rheumatic Disease in Latin American Indigenous Population: A Community Based Study. (15th July 2016) - Pelaez-Ballestas, I.; Granados, Y.; Silvestre, A.; Julian-Santiago, F.; Santana, N.; Rosillo, C.; Alvarez-Nemegyei, J.; Loyola-Sanchez, A.; Quintana, R.; Goycochea-Robles, M.V.; Pacheco-Tena, C.; Goñi, M.; et al.
Abstract : Background: GLADERPO group (Latin American Study Group on Rheumatic Diseases in Indigenous Peoples) is an organization aimed to conduct studies on indigenous populations with the purpose of closing the gap of information about rheumatic diseases and develop culturally-sensitive interventions. Objectives: Estimate the prevalence of musculoskeletal disorders and rheumatic diseases in eight Latinoamerican indigenous communities using the COPCORD methodology. Methods: A cross-sectional, house-by-house, community-based census study was performed. Bilingual staff members, who received standardized training, administered a cross-culturally validated version of the COPCORD questionnaire to adult indigenous population with the assistance of bilingual translators. Individuals with musculoskeletal pain, stiffness or swelling in the last 7 days and/or at any point during their lifetime were evaluated by participating physicians (general physicians and rheumatologist) to classify or diagnosed any rheumatic disease according to specific criteria. Results: We surveyed 6, 155 indigenous people having a mean age of 41.2 years (SD 17.6; range 18 to 105); 3, 757 (61.0%) were women. Mean education was 5.0 years (SD 4.1); and 4, 668 (75.8%) work for living. MSK pain in the past and during the last 7 days occurred in 2, 778 (45.1%; 95% CI 43.8–46.3) and 2, 127 individuals (34.5%, 95% CI 33.3–35.7%), respectively. Of these, 1, 195 (56.2%, 95% CI 54.1–58.3%) individuals associated pain to trauma. Pain was severe in 15.8% and according to localization, pain originated from the spine (26.7%), the knees (17.6%), shoulders (15.3%), and hands (10.6%) more frequently. Point-prevalence of main rheumatic diseases was: low back pain (LBP) in 821 (13.3%; 95% CI: 12.4–14.2); osteoarthritis (OA) in 598 (9.7%; 95% CI: 8.9–10.4); rheumatic regional pain syndromes in 368 (5.9%; 95% CI: 5.3–6.6); rheumatoid arthritis (RA) in 85 (1.3%; 95% CI: 1.1–1.7); systemic lupus erythematosus in 7 (0.1; 95% CI: 0.004–0.2); nonspecific arthritis in 13 (0.2%; 95% CI: 0.1–0.3); spondyloarthritis in 12 (0.1; 95% CI: 0.1–0.3); and scleroderma in 3 (0.04%; 95% CI: 0.01–0.1). There were marked variations in the prevalence of each rheumatic disease among the different communities, i.e.: RA prevalence was 2.4% in Qom (Argentina) and 0.4% in Mixtecos (Mexico). Conclusions: The overall prevalence of MSK disorders in indigenous community of Latin-American was 35.4%. Low back pain and OA were the most prevalent rheumatic conditions, but wide variations according to population groups occurred. Acknowledgement: National Council for Science and Technology (CONACYT)- Salud 2001–01–162154 (Mexico). Federico Wilhelm Agricola Foundation (Argentina). PDVSA East, SUELOPETROL and Bristol-Myers Laboratory (Venezuela). Disclosure of Interest: None declared